Acceptability and feasibility of a mobile health application for blood pressure monitoring in rural Uganda. - Mugabirwe, Beatrice; Flickinger, Tabor; Cox, Lauren; Ariho, Pius; Dillingham, Rebecca; Okello, Samson (JAMIA Open, 2020)
Background: Mobile technologies to improve blood pressure control in resource-limited settings are needed. We adapted and evaluated the acceptability and feasibility of Positive Links, a mobile phone application for self-monitoring, social support, and engagement in care for people living with HIV, among patients with hypertension in rural Uganda. Methods: We enrolled adults on treatment for hypertension at Mbarara Regional Referral Hospital and Mbarara Municipal health center IV, southwestern Uganda. We provided and educated all participants on the use of Positive Links application and automated blood pressure monitors. We administered a baseline questionnaire and performed in-depth interviews 30 days later to explore acceptability, feasibility, medication adherence, social support, and blood pressure control. Results: A total of 37 participants completed the interviews, mean age of 58 years (SD 10.8) and 28 (75.7%) were female. All participants embraced the Positive Links mobile app and were enthusiastic about self-monitoring of blood pressure, 35 (94.6%) experienced peer to peer support. Among the 35 participants non adherent to medications at baseline, 31 had improved medication adherence. All except 1 of the 31(83.8%) who had uncontrolled blood pressure at baseline, had self-reported controlled blood pressure after 30 days of use of Positive Links. Conclusion: Patients with hypertension in rural Uganda embraced the Positive Links mobile application and had improved medication adherence, social support, and blood pressure control. Further assessment of cost effectiveness of the application in blood pressure control in resource-limited settings will be pursued in future studies.
Keywords: Hypertension; Positive Links; Health; Feasibility; Acceptability; Self-monitoring; social support; Blood pressure control; Medication adherence